2021
DOI: 10.1002/bkcs.12431
|View full text |Cite
|
Sign up to set email alerts
|

Hexacoordinated Sn(IV) porphyrin‐based square‐grid frameworks exhibiting selective uptake of CO2 over N2

Abstract: We prepared porphyrin metal–organic frameworks with hexacoordinated Sn(IV) porphyrin trans‐SnX2(TPyP), where X = Cl−, OH−; TPyP = 5,10,15,20‐tetra(4‐pyridyl)porphyrinato dianion, and Cu(II) acetate, namely {[SnCl2(TPyP)]⋅[Cu(OAc)2]4}⋅4DMF⋅4H2O (1) and {[Sn(OH)2(TPyP)]⋅[Cu(OAc)2]4}⋅xSolv (2). X‐ray crystallographic analysis revealed that both materials consisted of the same square‐grid two‐dimensional (2D) sheet. The small difference in the trans‐axial ligand coordinated to the Sn(IV) center creates distinctive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…For example, the ideal adsorption selectivity of SnPOP was found to be as high as 21.2 for CO 2 /N 2 at 273 K and 23.1 for CO 2 /N 2 at 298 K. The selectivity of SnPOP at similar temperatures was comparable to or higher than that of recently reported porphyrin-based porous materials. The absorption isotherms clearly showed that SnPOP selectively absorbed CO 2 over N 2 , 13,57,58 which can be attributed to the dipole–quadrupole interaction between the organic functional groups present in SnPOP and the guest CO 2 molecules. The dispersion force within CO 2 molecules was significantly affected by their quadrupole moment or polarizability.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, the ideal adsorption selectivity of SnPOP was found to be as high as 21.2 for CO 2 /N 2 at 273 K and 23.1 for CO 2 /N 2 at 298 K. The selectivity of SnPOP at similar temperatures was comparable to or higher than that of recently reported porphyrin-based porous materials. The absorption isotherms clearly showed that SnPOP selectively absorbed CO 2 over N 2 , 13,57,58 which can be attributed to the dipole–quadrupole interaction between the organic functional groups present in SnPOP and the guest CO 2 molecules. The dispersion force within CO 2 molecules was significantly affected by their quadrupole moment or polarizability.…”
Section: Resultsmentioning
confidence: 96%
“…The multidimensional properties of these materials make them good alternatives to classical porous materials, such as zeolites, 5 metal oxides, 6 ceramics, 7 mesoporous silica, 8 and activated charcoal. 9 These materials have been extensively studied and utilized in various fields including heterogeneous catalysis, 10 gas storage, 11 biomedicine, 12 gas separation, 13 water purification, 14 electrochemistry, 15 and sensing. 16 POPs, which are highly cross-linked amorphous porous materials, are typically characterized by ample molecular-scale porosity (pore diameters ranging from a few nanometers to micrometers).…”
Section: Introductionmentioning
confidence: 99%
“…Within the carbon nitride family, polytriazine networks have been identified as having high surface area, high nitrogen content, and active sites that make them promising candidates for next-generation CO 2 capture. ,, The presence of amine functional groups, which can weakly adsorb CO 2 through acid–base interactions, in combination with the high specific surface area of these materials, further enhance their potential. , The introduction of point defects and metal doping can also create more exposed active sites and improve the performance of these materials. , …”
Section: Introductionmentioning
confidence: 99%
“…However, only in the last decade, chemically robust and permanently porous MPF materials have been achieved. [1,2] The designability of their structures, tunability of pore sizes and modularity of properties by crystal engineering strategy [3,4] as well as their permanent porosity afford them great potential for applications in gas storage and separation, [5][6][7] heterogeneous catalysis, [8,9] magnetism, [10] biomedical applications [11,12] or sensing. [13] Tetratopic and pentatopic square planar building blocks based on tetraarylporphyrins, such as 5,10,15,20-tetrakis(4pyridyl)porphyrin (H 2 TPyP) [14] and 5,10,15,20-tetrakis(4carboxyphenyl)porphyrin (H 6 TCPP), [15] have been used extensively as ligands in the synthesis of different MPFs with the almost all metal ions within the periodic table.…”
Section: Introductionmentioning
confidence: 99%